2015
DOI: 10.1007/s10689-015-9849-1
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1 and GSTP1 gene variations in breast cancer: a systematic review and case–control study

Abstract: In first part of this study, a systematic review was designed to explore the involvement of CYP1A1 and GSTP1 genes in breast cancerogenesis. Based on systematic review, we designed a study to screen CYP1A1 and GSTP1 genes for mutation and their possible association with breast carcinogenesis. A total of 400 individuals were collected and analyzed by PCR-SSCP. After sequence analysis of coding region of CYP1A1 we identified eleven mutations in different exons of respective gene. Among these eleven mutations, ~3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 179 publications
0
4
0
Order By: Relevance
“…Contrary to our results, some reports pointed out that there is a positive association between this polymorphism and risk of breast cancer. [143536] Noticeably, Sergentanis and Economopoulos conducted a meta-analysis on Caucasian, Chinese, and African populations, as well as on premenopausal and postmenopausal women to examine the correlation of CYP1A1 M2 polymorphism with breast cancer. The results demonstrated mutant genotype (GG) elevate risk of breast cancer and their results suggested that this polymorphism would be a good marker for prediction of breast cancer in these populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to our results, some reports pointed out that there is a positive association between this polymorphism and risk of breast cancer. [143536] Noticeably, Sergentanis and Economopoulos conducted a meta-analysis on Caucasian, Chinese, and African populations, as well as on premenopausal and postmenopausal women to examine the correlation of CYP1A1 M2 polymorphism with breast cancer. The results demonstrated mutant genotype (GG) elevate risk of breast cancer and their results suggested that this polymorphism would be a good marker for prediction of breast cancer in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Four SNPs in CYP1A1 gene including M1 (a nucleotide change at T3801 in the 3'-flanking region), M2 (A2455G at exon 7), M3 (T3205C in the 3'-flanking region), and M4 (C2453A at exon 7) are assumed to be associated with breast cancer. [1314] To date, these SNPs have not been evaluated in Mazandarani population. Hence, in the present case–control study, M2 polymorphism of CYP1A1 was studied for its association with breast cancer in Mazandarani population.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, single-stranded conformational polymorphism (SSCP) was used to analyze mutations in the polymerase chain reaction (PCR) products of the DNA extracted from white blood cells. Researchers have identified the involvement of CYP1A1 and GSTP1 in breast carcinogenesis [21]. Baldwin et al [22] developed a stable isotope labeling by amino acids in cell culture-based quantitative affinity purification/mass spectrometry approach to identify the interaction between PRMT1v1 and PRMT1v2 in BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…"Glutathione S-transferase P type 1" (GSTP1), an enzyme encoded by the GSTP1 gene, is responsible for the xenobiotic metabolism [121,122]. Recently, it has emerged as a potentially druggable target, especially in triple-negative breast cancers.…”
Section: Gstp1 Diet and Breast Cancermentioning
confidence: 99%